EKONOMI ISLAM SEBAGAI SOLUSI ARUS BARU EKONOMI INDONESIA (studi analisis atas pemikiran kyai makruf Amin): EKONOMI ISLAM SEBAGAI SOLUSI ARUS BARU EKONOMI INDONESIA (studi analisis atas pemikiran kyai makruf Amin) - Edy Tristiyanto (JOURNAL ISLAMIC ECONOMICS AD DIWAN, 2025)
The Islamic economic system is an independent economic system, therefore Islam encourages life as a whole and helps a person's life as an inseparable part of the life of society, whose individuals need each other and complement each other in the scheme of social order, because humans are both individual and collective entities. In accordance with its nature, Islamic economics is a system that can realize economic justice for all people. This study aims to understand and analyze: (1) Kyai Makruf Amin's thoughts on the Indonesian Economy (2) Kyai Makruf Amin's thoughts on Islamic economics in Indonesia (3) Kyai Makruf Amin's steps on his concepts and ideas about Islamic Law as a Solution for the new movement of the Indonesian economy. Therefore, the process of collecting research data is carried out by reading books, accredited scientific journals, literature, notes, and reports and other relevant sources related to the problem being studied. The data obtained are then recorded, studied, reviewed and analyzed. Data analysis is carried out by content analysis. The findings of the research show that: Kyai Ma'ruf Amin named his idea the New Current of Indonesian Economy. A conceptual idea that has also been equipped with program recommendations, so that it can be lightly labeled with the term Ma'rufnomics. Aiming to overcome inequality in order to realize a just people's economy, he is actually revitalizing the people's economy, so it is necessary to always emphasize his support in building a fair, equitable, and independent national economic system in overcoming economic disparities. According to Kyai Makruf, the four concepts regarding the new current of economy must be able to practice the 5th principle of Pancasila, namely social justice for all Indonesian people.